Respostas agudas do exercício físico em pessoas com HIV/AIDS: efeitos sobre parâmetros imunológicos e fisiológicos - Melo, Bruno Pereira (2015)
The practice physical exercise has been recommended to promote health and to reduce the development of chronic degenerative disease. However, excess exercise and inappropriate prescription may result in physiological changes that not controlled can result to health problems. Although the practice the physical exercise has been widely recommended in people infected with HIV, the physiological and immunological changes in short term resulting of the exercise were little investigated, difficulting a prescription safely and efficiently for this population. Therefore, we aimed to investigate the acute responses to exercise in people with HIV. For this, two studies were conducted, a systematic review of the acute effects of different types of exercise (aerobic, resistance and combined) and an experimental study in which it aimed to verify the acute responses resulting from the combined training on physiological parameters and immunological in sedentary adults infected or not infected by HIV. According to the studies conducted and the results obtained in this work, observed that physical exercise promotes significant acute changes in various immune and physiological parameters in HIV-infected people, including increasing the number of circulating cells mainly total neutrophils, monocytes and lymphocytes TCD8+, as well as changes in the concentrations of lactate, triglycerides, epinephrine and norepinephrine immediately after the aerobic training. Furthermore, it was found that the combined training promotes a decrease in variability indices of the heart rate and of cortisol levels after 1 and 6 hours after completion of the training combined respectively. However, not there were significant differences in the behavior of blood pressure and the concentrations of cytokines of action pro action and anti-inflammatory even after 6 hours of the combined training when compared infected and HIV-uninfected. Therefore, it is concluded that exercise promotes significant changes in various physiological and immunological parameters in independent sedentary adults HIV infection. However, the magnitude of these changes can be directly related to the type, intensity and volume of exercise, beyond the physical capacity and the clinical status of each person. In this sense, it is recommended that the prescription of exercise training for people with HIV should be performed with caution, taking into account the clinical status and physical fitness of each patient, suggesting the model of training combined with moderate intensity for this population.